2018
DOI: 10.1080/15568318.2018.1481547
|View full text |Cite
|
Sign up to set email alerts
|

Conditions for electric vehicle taxi: A case study in the Greater Stockholm region

Abstract: This study investigates the usability of electric vehicles (EVs) in a taxi company in Greater Stockholm, Sweden. By investigating cost and revenue data of both electric and conventional taxi vehicles, as well as by interviewing taxi drivers and carriers, an assessment has been made of the financial and operational implications of using EVs in a company's taxi fleet. Both the drivers' and the carriers' perspectives have been examined. The main findings are that the investigated e-taxis have a similar or lower T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…30 In India, the TNC company Ola launched a highly publicized pilot with BEVs in the city of Nagpur but ended the project prematurely due to driver strikes arising from long queues at charging stations and lost revenue. 31 In both Stockholm 32 and San Francisco, 33 drivers have reported declining rides because their vehicles lacked sufficient charge as well as revenue losses owing to time spent charging and looking for charging stations. Current understanding is that fast-charging infrastructure is prohibitively expensive to build and operate without high levels of public subsidy, but the truth is more complex.…”
Section: ■ Modv Electrification Lacks Adequate Policy Supportmentioning
confidence: 99%
“…30 In India, the TNC company Ola launched a highly publicized pilot with BEVs in the city of Nagpur but ended the project prematurely due to driver strikes arising from long queues at charging stations and lost revenue. 31 In both Stockholm 32 and San Francisco, 33 drivers have reported declining rides because their vehicles lacked sufficient charge as well as revenue losses owing to time spent charging and looking for charging stations. Current understanding is that fast-charging infrastructure is prohibitively expensive to build and operate without high levels of public subsidy, but the truth is more complex.…”
Section: ■ Modv Electrification Lacks Adequate Policy Supportmentioning
confidence: 99%
“…This may be achieved through municipal activities to stimulate large users of taxis (e.g., hotels and large businesses) to only select electric taxis [11]. An example of such an initiative is described by Hagman and Langbroek [12] for the city of Stockholm. Increasing demand for electric taxis can furthermore be achieved by creating zero-emission taxi stands, as has also been done in Amsterdam [13].…”
Section: Situational Factorsmentioning
confidence: 99%
“…In their research on the implementation of EVs within a commercial fleet, Wikström and colleagues show that current EV users can act as ambassadors to promote EV usage, but that co-workers who were less enthusiastic about using an EV could not be persuaded by their ambassador colleagues [30]. In the context of electric taxis, Hagman and Langbroek [12] acknowledge the lack of information on electric taxis in regard to profitability, requirements and limitations.…”
Section: Psychological Factorsmentioning
confidence: 99%
“…In a London pilot project, Uber found that over 80% of BEV drivers lacked access to home charging, and insufficient public infrastructure prevented drivers from serving as many rides as they could with internal combustion engine vehicles (ICEVs) [10]. Furthermore, transportation network company (TNC) drivers with BEVs have reported declining rides because their vehicles lacked sufficient charge as well as revenue losses owing to time spent charging and looking for charging stations [11], [12]. In a study in South Korea, BEV taxis provided a lower benefit-to-cost ratio compared with natural-gas-powered taxis because of limited charging infrastructure and battery range [13].…”
Section: Introductionmentioning
confidence: 99%